The Mediating Role of Commitment to Enhance Project Performance in Indonesia’s Construction Industry - Alldo HW; William Mangapul Hasiholan; M. Nefriansyah Hasibuan; Jerry S. Justianto (International Research Journal of Business Studies, 2025)
The construction industry in Indonesia is growing rapidly, with significant projected growth in 2025. However, delays and failures in project completion remain major challenges, negatively impacting companies and the industry's reputation. This study aimed to analyze the influence of emotional intelligence and organizational culture on project performance, with organizational commitment as a mediating factor, focusing on project managers in state-owned construction companies. Using a quantitative-explanatory approach and probability sampling with cluster techniques, data were collected from 166 project managers across seven state-owned construction firms in Indonesia. SEM-PLS was employed for analysis. Results indicated that emotional intelligence significantly impacts both project performance and organizational commitment. Additionally, organizational culture promoting transparency and collaboration positively influences project performance, albeit to a lesser extent. Organizational commitment serves as a critical mediator. Future studies should consider demographic factors, adopt a longitudinal design, and involve broader organizational roles for a more comprehensive perspective.